Ціннісно-нормативні моделі міського середнього класу в Україні (за даними компанії TNS) - Сальнікова, Світлана Анатоліївна; Сальникова, Светлана Анатольевна; Salnikova, Svitlana А.; Хомяк, Андрій Олександрович; Хомяк, Андрей Александрович; Khomiak, Andrii O. (My University, 2016)
Розглянуто середній клас як рушійну силу суспільства – високоосвічену, професійну, а отже, інноваційну, винахідливу, схильну до ризиків, при цьому будучи відносно забезпеченими, його представники більшою мірою здатні до розв’язання суспільно значимих проблем. За даними компанії TNS Ukraine (2015), ідентифіковано середній клас (11,9 % серед дорослого 16+ населення міст) та обґрунтовано його наявність відмінними від решти прошарків соціально-демографічною структурою й ціннісно-нормативною системою. За допомогою факторного аналізу та аналізу надійності виокремлено такі статистично значущі ціннісно-нормативні моделі, як модель професійної престижності (представлена показниками матеріальної зорієнтованості, стимуляційного суперництва, престижного вигляду, первинності кар’єри та успіху); модель готовності до інновацій (використання передових технологій, підприємництво, придбання техноновинок, первинність інтересу успіху); модель готовності ризикувати (цільовий ризик, гострота відчуттів, подолання труднощів, готовність до змін); модель соціальної відповідальності (соціальна активність, захист довкілля, індивідуальна впливовість). За кожною моделлю побудовано усереднений індекс, кожен є валідним та надійним; усі також виявились узгодженими та скорельованими. By considering different approaches to the definition of the middle class, authors examine it as a driving force of society – highly educated, professional and, therefore, innovative, inventive, able to risk. At the same time, being relatively wealthy, its representatives are more able to solve socially significant problems. According to empirical data of TNS Ukraine company (2015) the authors have made an empirical identification of the middle class (11,9 % of the adult population 16+ from cities in Ukraine). They validate existence of middle layer by identifying its socio-demographic structures and value-normative systems that are different from other layers. In particular, statistically significant differences in age and educational structures, locality type, as well as in the sphere of production activity were identified. By using factor analysis and analysis of reliability, the authors selected the following statistically significant value-normative models: − Professional Prestige Model, presented by indicators of material orientation, stimulant competition, prestigious appearance, antecedence of career and success; − Readiness for Innovations Model (the use of advanced technology, entrepreneurship, purchase of new technologies, antecedence of success interest); − Model of Willingness to Take Risks (target risk, sharpness of feeling, the overcoming difficulties, readiness to change); − Model of Social Responsibility (social activity, environmental protection, individual influence). The authors constructed average indexes on correspondent indicators, the each index based on the certain model; the indexes are valid and reliable. Consistency of all indexes and correlation between them is an additional result that is the reason for construction the total index and making further researches in order to find value-normative differences among cohorts of middle class and other layers.
Value-Normative Models of the Urban Middle Class in Ukraine (according to the Empirical Data From TNS)
Keywords: індекс; вимірювальна модель; факторний аналіз; аналіз надійності; ідентифікація середнього класу; Index; measurement model; Factor Analysis; Reliability Analysis; Identity of Middle Class